Advances in parasitology. Volume 43 - Muller, R.; Baker, J. R.; Rollinson, D. (London ; New York : Academic Press, 1999)
Advances in Parasitology is a series of up-to-date reviews of all areas of interest in contemporary parasitology. It includes medical studies on parasites of major influence, such as typanosomeiasis and scabies, and more traditional areas, such as zoology, taxonomy, and life history, which shape current thinking and applications.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Protozoa, pathogenic; Protozoan diseases; Protozoa, Pathogenic; Protozoan diseases; Electronic books